2018
DOI: 10.1016/j.jid.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Co-Activation of Glucocorticoid Receptor and Peroxisome Proliferator–Activated Receptor-γ in Murine Skin Prevents Worsening of Atopic March

Abstract: Children with atopic dermatitis show an increased risk to develop asthma later in life, a phenomenon referred to as "atopic march," which emphasizes the need for secondary prevention therapies. This study aimed to investigate whether relief of skin inflammation by glucocorticoids and peroxisome proliferator-activated receptor agonists might influence the subsequent development of asthma in a murine model for the atopic march in which mice were repeatedly exposed to house dust mite via the skin, followed by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…By this, steps are undertaken to develop therapies that stimulate only the wanted anti-inflammatory GC-functions without inducing the broad and also the unwanted GC-effects (212). Further, studies also invest in the therapeutic potential of combination therapies, such as the combination of GR and PPAR agonists (213, 214).…”
Section: Gc Therapy: Drawbacks and Optimizationmentioning
confidence: 99%
“…By this, steps are undertaken to develop therapies that stimulate only the wanted anti-inflammatory GC-functions without inducing the broad and also the unwanted GC-effects (212). Further, studies also invest in the therapeutic potential of combination therapies, such as the combination of GR and PPAR agonists (213, 214).…”
Section: Gc Therapy: Drawbacks and Optimizationmentioning
confidence: 99%
“…The results of the present study demonstrated that dex inhibited cell proliferation, followed by the induction of keratinocyte apoptosis. GC mainly binds GRs and influences cell proliferation or cell damage (43); although a number of GRs are located in skin keratinocytes (44), previous studies have identified the positive effects of Dex in atopic dermatitis and wound healing (45,46). However, another study has reported that an elevated concentration of dex decreased cell proliferation and induced apoptosis and/or necrosis in endothelial cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…These interesting findings rise the questions to which extent keratinocyte-derived GCs are capable of modifying the initial progress of atopic march diseases in the lung and intestine during early skin sensitization phases and draining lymph node priming (12,65). Specifically, it is of interest to explore the impact of skin GCs on developing and chronic AD, and whether and how they affect the differentiation of T H 2 cells and innate type 2 immune cells in the skin.…”
Section: The Perspective Of Gcs To Regulate Pathogenic Crosstalk In the Atopic Marchmentioning
confidence: 99%
“…This may also explain why clinical application of potent high-class GCs are efficient in the treatment of acute allergic reactions in skin, and at mucosal sites of the airway and intestine despite the inefficiency of endogenous local GCs to completely shut down experimental type 2 inflammation. In this regard, a recent study described an experimental model for atopic march using mice with HDM-induced chronic AD skin conditions and subsequent allergic airway inflammation upon HDM challenge ( 65 ). This study revealed that co-activation of both GR and PPARγ using dexamethasone and the PPARγ-ligand rosiglitazone was more efficient in suppressing AD skin inflammation than single nuclear receptor activation ( 65 ).…”
Section: Tissue-immune Regulation and Interorgan Crosstalkmentioning
confidence: 99%